Perancangan Set Produk Interior Ergonomis Untuk Profesional Gamer - Fabian Ryan Santoso; Grace Mulyono; Frenky Tanaya (Intra, 2018)
Ergonomic Interior Product Set Design for Professional GamersThe development of technology, especially in the world of games today leads to the rise of many organizations and professionals concerned in gaming world competitions. Professional athletes that appears from the organizations in the gaming world requires special supporting facilities in order to do their gaming activity well. Therefore it takes support facilities, especially on ergonomic interior products that can help gamers in doing their activities play. The formulation of the problem that must be solved is how to design gamers working facilities that fit the needs of professional gamers.Design using Nielsen Norman Group method in the process of design thinking to get data and solutions about the needs of gamers in doing their activities. There are several alternative designs to be an alternative in the selection of design, function and innovation of different designs. The design of the design focuses on creating new innovations, through the use of technology that is currently being developed. So as to create convenience, practicality, and comfort to perform activities especially intended for professional gamers.